(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Libraries are growing from web 2.0 to web 4.0 with complete metamorphosis in terms of theacquisition, processing to services. Subject librarian concept modified with research and researchmethods related queries to pay the role of research librarian. The Library professional involve in thisresearch supportive activity is the Library researcher or research librarian. He marketing hisher libraryservices and same time tries to establish connections or partnerships for research base activity.Interdisciplinary approach is growing more today. This embedded, collaborative role may strengthen theacademic librarians to sustain with time and to grow an important agenda of parent institute.